Pure Formamidinium‐Based Perovskite Light‐Emitting Diodes with High Efficiency and Low Driving Voltage. Issue 4 (23rd November 2016) - Meng, Lei; Yao, En‐Ping; Hong, Ziruo; Chen, Huajun; Sun, Pengyu; Yang, Zhanlue; Li, Gang; Yang, Yang
Abstract : A formamidinium(FA)‐based perovskite showns superior optoelectronic properties including better stability than methylammonium‐based counterparts. Pure FA‐perovskite‐based light‐emitting diodes (LEDs) with high efficiency are reported. Interestingly, the LED clearly shows a sub‐bandgap emission at 1.7 V (bandgap 2.3 eV). This important discovery provides further insights of the charge transport mechanism in perovskite‐based optoelectronic devices.